2020
DOI: 10.1016/j.jctube.2020.100200
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of depression in patients with drug-resistant tuberculosis in Nepal: A cross-sectional study

Abstract: Highlights Patients with drug-resistant tuberculosis (DR TB) are at high risk for depression. DR TB patients in Nepal were screened with Health Questionnaire 9 for depression. 81 out of 129 patients (62.7%) were found to have possible depressive disorder. Duration of illness was a significant risk factor for depression ( p < 0.001).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 19 publications
1
5
1
1
Order By: Relevance
“…A study from India however reported a low prevalence of depression in TB patients 16.2. 14 A study 18 conducted in Nepal reported the prevalence of TB 62.7% which is comparable to our findings.…”
Section: Discussionsupporting
confidence: 90%
“…A study from India however reported a low prevalence of depression in TB patients 16.2. 14 A study 18 conducted in Nepal reported the prevalence of TB 62.7% which is comparable to our findings.…”
Section: Discussionsupporting
confidence: 90%
“…In our study, the prevalence of depression among people with TB at baseline (end of intensive phase) and follow-up (end of continuation phase) was higher than other cross-sectional studies conducted in Nepal (10%) and China (18%) but similar to Nigeria (28%) and Vietnam (25%) [44,[80][81][82]. The differences in depression prevalence across countries may relate to the time point during TB treatment at which the depression scale was applied and also to sociodemographic differences including urban or rural location, age, gender, inadequate social support, and low education status [83].…”
Section: Depressioncontrasting
confidence: 66%
“…We selected covariates a priori based on previous studies demonstrating that these covariates correlate with prognosis and/or rates of toxicities in aggressive NHL [22][23][24][25][26][27]. We then conducted multivariable logistic regression analyses including all covariates with a value of p < .25 in univariate analyses [28,29]. We included treatment regimen in the multivariable model of grade 3-5 nonhematologic toxicity given the established association of treatment regimen with grade 3-4 adverse events [26].…”
Section: Discussionmentioning
confidence: 99%